'The finest set of cup and ring marks in existence': the story of the Cochno Stone, West Dunbartonshire. Issue 1 (March 2018) - Brophy, Kenneth
Abstract : The Cochno Stone is one of the most extensive and highly decorated prehistoric rock-art outcrops in Britain. It is located on the northern urban fringe of West Dunbartonshire beside Faifley, Clydebank, in a park in the foothills of the Kilpatrick Hills. First re-discovered by antiquarians toward the end of the nineteenth century, this outcrop subsequently became the focus of the attentions of Ludovic McLellan Mann in the 1930s, who decorated the stone with an elaborate painted colour-scheme. Expanding urbanisation, visitor numbers and graffiti prompted the authorities to bury the stone beneath soil for its own protection in 1965. During two seasons of fieldwork in 2015 and 2016, the Cochno Stone was exposed for short periods of time to allow for an assessment to be made of the condition of the stone surface, and digital and photogrammetric recording to take place. Provisional results of the fieldwork are reported on here, but the main focus of this paper is to present as fully as possible for the first time the biography of the Cochno Stone from antiquarian discovery to the present day. The paper concludes with thoughts about the future of this monument.